Analisis Faktor Determinan Kejadian Stunting pada Balita di Desa Siau dalam Kabupaten Tanjung Jabung Timur - Fadliyana Ekawaty; Sri Mulyani (Universitas Batanghari Jambi, 2022)
Stunting is a condition where there is a failure in growth caused by inadequate nutritional intake and is caused by a history of infectious diseases that always repeat in life. The first thousand days. Siau Dalam Village is a stunting locus village in Tanjung Jabung Timur Regency, Jambi Province. Identify the determinants of factors related to stunting in the age range of 12-59 months. The sample technique in this study used a total sampling of 49 stunting children (as a case group). for the control group, it was carried out using purposive sampling totaling 49 children who were not stunted. From multivariate analysis, the determinants of stunting in children aged 12-59 months were maternal education (p= 0.005; OR= 11.956), low birth weight (p= 0.047; OR= 10.135), history of infection (p=0.009; OR= 3,680). Mothers with low education will be at risk of having stunting toddlers compared to mothers with higher education. Mothers with higher education will show good parenting in sorting out good nutrition for their children. Maternal education, birth weight, history of infection are determinants of stunting in Siaudalam Village, It is recommended for Health Workers in this case nurses to provide insight in the form of information and education from many sources through informal education in the form of workshops, webinars so that they can provide mother's understanding of stunting